Deciphering cellular biological processes to clinical application: a new perspective for Tα1 treatment targeting multiple diseases. (31st May 2018) - Matteucci, Claudia; Argaw-Denboba, Ayele; Balestrieri, Emanuela; Giovinazzo, Alessandro; Miele, Martino; D'Agostini, Cartesio; Pica, Francesca; Grelli, Sandro; Paci, Maurizio; Mastino, Antonio; Sinibaldi Vallebona, Paola; Garaci, Enrico; et al.
ABSTRACT: Background : Thymosin alpha 1 (Tα1) is a well-recognized immune response modulator in a wide range of disorders, particularly infections and cancer. The bioinformatic analysis of public databases allows drug repositioning, predicting a new potential area of clinical intervention. We aimed to decipher the cellular network induced by Tα1 treatment to confirm present use and identify new potential clinical applications. Research design and methods : We used the transcriptional profile of human peripheral blood mononuclear cells treated in vitro with Tα1 to perform the enrichment network analysis by the Metascape online tools and the disease enrichment analysis by the DAVID online tool. Results : Networked cellular responses reflected Tα1 regulated biological processes including immune and metabolic responses, response to compounds and oxidative stress, ion homeostasis, peroxisome biogenesis and drug metabolic process. Beyond cancer and infections, the analysis evidenced the association with disorders such as kidney chronic failure, diabetes, cardiovascular, chronic respiratory, neuropsychiatric, neurodegenerative and autoimmune diseases. Conclusions : In addition to the known ability to promote immune response pathways, the network enrichment analysis demonstrated that Tα1 regulates cellular metabolic processes and oxidative stress response. Notable, the analysis highlighted the association with several diseases, suggesting new translational implication of Tα1 treatment in pathological conditions unexpected until now.